STUDI TENTANG USAHA SEPRAI PENGANTIN (Studi Kasus Pada Industri Arinda Kelurahan Bulakan Balai Kandi Kecamatan Payakumbuh Barat Kota Payakumbuh) - Dwi, Retno Desti; Efi, Agusti; Idrus, Yenni (Journal of Home Economics and Tourism, 2013)
Manufacture bridal sheets relating to human resources and quality control. This study aimend to decribe the human resources and quality control in the linen business in the bridal industry Bulakan Arinda Vilage center district west Payakumbuh Kandi Payakumbuh. Methods used in this research in deskriptive qualitative methods. Types of data in the from of primary and secondary data. Techniques of data collection through observation, interview and documentation, drawing conclusions. The results of this study are: (1) human resources in the industry Arinda come from low economic backgrounds, educational levels from elementary through high shcool, the knowledge and skills that they can sew from sewing, to self development. (2) quality control in industry Arinda has not gone up with the complaints consumer about result that is less neat stitching, becouse the quality control was not optimal, this is due to the tailor sew in their homes each so overall less observed. Kata Kunci : Usaha, Seprai Pengantin, Industri Arinda